The Analysis of the Criminal Case Transfer Procedure from Investigators to Public Prosecutors in the Prosecution Stage (Stage II) - Manurung, Berliana Feronika; Siregar, Hisar (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
In the Indonesian criminal justice system, there are several stages in the mechanism for handling a criminal case. The first stage is the examination, also known as the investigation and inquiry conducted by the police, which is then transferred to the prosecutor's office for further investigation and finally to the process of transfer to the court and finally to trial. The purpose of this study is to determine the procedure for transferring criminal cases from investigators to public prosecutors in stage II according to the Criminal Procedure Code and the procedure for handing over and investigating suspects by investigators to prosecutors in a brief examination procedure. The method used is a qualitative method. The results of this study are about how the case examination procedure according to the Criminal Procedure Code and how the procedure for transferring cases in a brief examination procedure. First, the Case Examination Procedure according to the Criminal Procedure Code in Chapter XVI differentiates the case examination procedure in district court trials. Basically, the starting point for this difference in examination procedures is reviewed from the type of crime being tried on one side and from the ease or difficulty of proving the case in question on the other side, the Procedure for Transferring Cases in a Brief Examination Procedure. Regarding the brief examination procedure, in the Criminal Procedure Code (Law No. 8 of 1981), it is regulated in Articles 203 and 204. From the results of the study, it can be concluded that the procedure for brief case examination is generally guided by the ordinary examination procedure. The Criminal Procedure Code does not provide limitations on which cases are included in the ordinary examination. In the examination of cases in the brief examination procedure, the public prosecutor does not make an indictment but the public prosecutor immediately after the defendant in court answers the questions then informs the defendant verbally from his notes about the crime charged to him by explaining the time, place and circumstances when the crime was committed.